2008
DOI: 10.1364/oe.16.021132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of motion of an imaging system and optical image stabilizer on the modulation transfer function

Abstract: This paper analyzes the effects due to the angular motion of a small-sized imaging system equipped with an optical image stabilizer (OIS) on image quality. Accurate lens moving distances for the OIS required to compensate the ray distortion induced by the angular motion are determined. To calculate the associated modulation transfer function, the integrated and the compensated point spread functions are defined. Finally, the deterioration of the image resolution due to angular motion and the restorative perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Kauhanen and Rouvinen (2006) reported that the handshake of a mobile device was 1.7°and 0-30 Hz. Choi et al (2008) reported that the stroke of the actuator is dependent on the optical imaging system. A drive integrated circuit was considered, which is used in the OIS actuator, and the desired specifications of the OIS actuator and the performance of the conventional actuator are summarized in Table 1.…”
Section: Mechanism Designmentioning
confidence: 99%
“…Kauhanen and Rouvinen (2006) reported that the handshake of a mobile device was 1.7°and 0-30 Hz. Choi et al (2008) reported that the stroke of the actuator is dependent on the optical imaging system. A drive integrated circuit was considered, which is used in the OIS actuator, and the desired specifications of the OIS actuator and the performance of the conventional actuator are summarized in Table 1.…”
Section: Mechanism Designmentioning
confidence: 99%
“…The yaw and pitch angle of the camera is converted into the lens displacement which is generated by the OIS actuator as given in Eq. (1) (Choi et al 2008).…”
Section: The Specification Of the Ois Actuatormentioning
confidence: 99%
“…They reduce camera resolution and cause image obscuring. For decreasing image shifts, stability of satellite is usually controlled by all kinds of technologies, thus increasing heavily the cost and enlarging the size and weight of the satellite [4,5].…”
Section: Introductionmentioning
confidence: 99%